Which Clouds Have Silver Linings? Fixed-Term Employment, Psychological Distress, and Occupational Position in Poland - Kiersztyn, Anna (International journal of sociology, 2016)
In recent years, many studies have attempted to assess the relationship between contractual status and a range of well-being outcomes, including self-reported health status or psychological distress. These studies have generally failed to establish a conclusive, straightforward link between working on a fixed-term contract and subjective quality of life. In light of these results, further attention needs to be paid to the heterogeneity of temporary jobs in terms of working conditions and the career prospects they offer. This article examines the occupational differences in the effects of fixed-term employment on the psychological condition of workers, bringing together two separate lines of research: on the psychological consequences of fixed-term employment and the structural and institutional determinants of the wage effects and career consequences of temporary jobs. The analyses are based on data from the past two waves of the Polish Panel Survey POLPAN, 2008 and 2013. POLPAN is the only Polish survey that includes detailed information on the type of employment contract, as well as multidimensional indicators of mental health (components of the Nottingham Health Profile). The mixed empirical results give rise to important insights into the complex links between employment flexibility and occupational inequalities on the Polish labor market.